The problem of developing the communicative skills of foreign students in a multicultural educational environment - Жань, Цао; Сарсенбаева, Лязиза (Pedagogy and Psychology, 2021)
The article presents an analysis of the state of the problem of development of communication skills of foreign students from the position of inclusion in the multicultural educational environment of higher education institutions. The article reveals such aspects of the problem as terminological diversity, the role of communication skills in the assimilation of social experience and in personal and professional development. Approaches to determining the structure and types of communication skills are considered. The author’s definition and structure of communication skills of foreign students are proposed. The article analyzes modern research of scientists from foreign countries, China, Russia and Kazakhstan, devoted to the study of the features and psychological and pedagogical conditions for the formation of communication skills of foreign students in a multicultural educational environment.